Locally Procured Wild Game Culinary Trends in the US: A Study of the Ruffed Grouse as Entrée and Accompanying Nutritional Analysis - Tidball, Keith G.; Tidball, Moira M.; Curtis, Paul D. (Frontiers in Sustainable Food Systems, 2022)
Wild-caught foods including game and fish can be part of a local, sustainable food system. Beneficial environmental, personal health, and nutrition claims are often linked to locally-sourced foods. Yet, because many species of wild game and fish that are legal to hunt or catch do not have nutrient data in the USDA food composition database these claims, especially in the realm of nutrition, are not well substantiated. To address this gap, the Cornell research team collaborated with USDA scientists to address shortcomings in nutrition information for several wild game and fish species, in this case Ruffed Grouse. A wildlife biologist with the Ruffed Grouse Society collected bird samples according to USDA-determined collection protocols to obtain edible meat portions. Nutrient analysis was conducted on raw Ruffed Grouse breast meat samples at USDA-validated laboratories using approved quality assurance procedures. Analytical data were sent to NDL scientists, who reviewed and compiled the data into full nutrient profiles for Ruffed Grouse which were made available in the USDA food composition database. This new nutritional information supplements the already-well-appreciated epicurean qualities of the Ruffed Grouse and contributes to the complex social construction of the notion of hunted food as gourmet entrée.